(untitled) (Bangladesh Journal of Animal Science, 2016)
The experiment was conducted to investigate the present status of organic beef cattle production at Shahjadpur upazilla of Sirajgonj district in Bangladesh through field survey. The data were collected based on a prescribed interview schedule from 30 respondents selected from 6 villages of Shahjadpur upazila who were involved in beef cattle production. Parameters studied were origin, feeds and fodder, breeding, health care, animal welfare and other factors related to organic beef cattle production. In this study, 12% cattle were indigenous and 88% crossbred in origin. 83% farmers used cultivated fodder and 17% used cultivated and roadside grass which was cultivated in their own land. However, 37% farmers used vitamin mineral supplementation. Among the farmers, 13% farmers used natural breeding, 73% farmers used A.I. and 14% both methods for livestock breeding. 87%, 80%, and 83% farmers practiced vaccination, deworming and grooming, respectively while, 70% farmers used hormone, antibiotic and growth promoter for beef cattle production and only 33% farmers isolate sick or injured animal from healthy stock. 73% farmers allowed access to outdoor and pasturing during winter season and only 3% farmers kept their livestock record. 37% farmers purchase cattle occasionally and 53% farmers fattened cattle for 3 months and rest fattened for a prolonged period. In Bangladesh beef cattle are fatten in conventional method where different inorganic substances are used by the farmers. So there are great potentialities for organic beef cattle production in Bangladesh both for satisfying animal protein requirement and production of quality beef. Bang. J. Anim. Sci. 2016. 45 (1): 25-30